Validation of the food frequency questionnaire for the assessment of dietary vitamin D intake - Hribar, Maša; Žlavs, Katarina; Pravst, Igor; Žmitek, Katja (Frontiers in Nutrition, 2022)
Vitamin D and its adequate status are related to many aspects of human health; therefore, an appropriate tool is needed for the valid assessment of vitamin D status. The main contributor to vitamin D status is endogenous synthesis after cutaneous exposure to ultraviolet B light (UVB), but in the absence of UVB radiation, vitamin D intake becomes an important source of vitamin D. Various tools are available for vitamin D intake assessments, with the Food Frequency Questionnaire (FFQ) being among the fastest, cheapest, and most convenient; however, until now, these tools have not been adapted for the Slovenia (SI). To enable valid vitamin D intake estimation, we developed a simple one-page semi-quantitative FFQ (sqFFQ/SI) and tested its validity using a five-day dietary record (DR) as a reference method. The reproducibility was tested with the second sqFFQ/SI (sqFFQ/SI2) six weeks after the first (sqFFQ/SI1). The validity and reproducibility of this method were tested on 54 participants using Bland-Altman plots, Spearman’s correlation, and Kappa analyses of tertiles. The mean daily vitamin D intake was 3.50 ± 1.91 µg according to the five-day DR, and 2.99 ± 1.35 µg and 3.31 ± 1.67 µg according to the sqFFQ/SI and repeated sqFFQ/SI (sqFFQ/SI2), respectively. When analysing for validity, the sqFFQ/SI was found to be significantly correlated (p< 0.05) with the five-day DR, with an acceptable correlation coefficient of 0.268 and a Bland–Altman index of 3.7%. For reproducibility, the correlation between the sqFFQ/SI and sqFFQ/SI2 was highly significant (p<0.001), with a good correlation coefficient of 0.689 and a Bland–Altman index of 3.7%. Kappa analyses of tertiles showed a poor validity and acceptable reproducibility. Overall, we observed a higher reproducibility than validity. Validation and reproducibility analyses demonstrated that the proposed sqFFQ/SI is acceptable and is, therefore, an appropriate tool for the effective assessment of habitual vitamin D intake on an individual level. With this consideration, this tool will be used in further population studies to assess vitamin D intake and for the development of screening tool for the assessment of the risk for vitamin D deficiency, which will be used as a foundation for policy-making decisions.